Hungarian Monitoring, 4 January 1989 . [Magyar rádiófigyelő], 1989. január 4 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - American-Libyan conflict - American-Libyan relations as seen by Moscow - Libyan chemical weapons factory - Inflation and serious imbalance in Poland - Foreign advertisements break into the Soviet press - "Republicans" fascist advertisement on West Berlin TV - Rude Pravo on Hungarian social changes Domestic Affairs: - Jenő Váncsa in Israel - Patriotic Popular Front Budapest presidium proposes dual candidates József Bielek and Lajos Urbán as Budapest Council president - Criminal law code before modification - Vatican-Hungarian relations - Portrait film of Otto Habsburg in the cinemas - Interview with a young AIDS carrier Economy: - Central Statistical Office (KSH) brief statement on 1988 - Danubia Engineering Works Company faces product restructuring - Budapest Council committee investigates whether it is worthwhile to transfer 40-50% of the trade and services sector into private hands - Professional discussion at Comecon on questions of necessary modernizations Külpolitika: - Az amerikai-líbiai konfliktus - Az amerikai-líbiai viszály moszkvai szemszögből - A líbiai vegyi fegyver gyár ügye - Infláció és súlyos egyensúlyhiány Lengyelországban - A külföldi hirdetések betörtek a szovjet sajtóba - A "Republikánusok" fasiszta reklámja a nyugat-berlini TV-ben - A Rude Pravo a magyar társadalmi változásokról Belpolitika: - Váncsa Jenő Izraelben - A HNF budapesti elnöksége kettős jelöléssel Bielek Józsefet, valamint Urbán Lajost javasolja a fővárosi tanács elnökének tisztségére - Módosítás előtt a BTK - Vatikáni-magyar kapcsolatok - Mozikban a Habsburg Ottóról készült portréfilm - Interjú egy AIDS-beteg fiatalemberrel Gazdaság: - KSH-gyorsjelentés az 1988-as évről - A Danubia Gépipari Vállalat termékszerkezet váltás előtt áll - A fővárosi tanácsnál bizottság vizsgálja, hogy érdemes lenne-e a kereskedelmi és szolgáltató szektor 40-50 %-át magánkézbe adni - Szakmai vitaülés a KGST-ben szükséges korszerűsítések kérdéseiről